(untitled) (Bangladesh Journal of Botany, 2015)
The volatile constituents of the leaves of Anethum graveolens L., growing wild in Iran, were investigated by GC/MS, ?-Phellandrene (29.12%), limonene (26.34%), dill ether (15.23%), ?-pinene (2%), n-tetracosane (1.54%), sabinene (1.34%), neophytadiene (1.43%), n-docosane (1.04), n-tricosane (1%), n-nonadecane (1%), n-eicosane (0.78%), n-heneicosane (0.67%), ?-myrcene (0.23%) and ?-tujene (0.21%) were found to be the major constituents of the oil. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22742 Bangladesh J. Bot. 44(1): 159-161, 2015 (March)